Working with students who have anxiety creative connections and practical strategies - Johns, Beverley Holden 1940-; Heise, Donalyn; Hunter, Adrienne (Eye on Education book, 2020)
As the number of students with anxiety increases in schools and classrooms, this book serves as the go-to guide for teachers and educators who strive to provide a welcoming environment conducive to students' learning. Working with Students Who Have Anxiety provides an accessible understanding of anxiety in its various forms, how anxiety impacts academic and social skills, and what teachers can do to create a positive climate. An exciting new resource for teachers, special educators, art specialists, and school counselors, this book covers the causes, signs, and symptoms of anxiety; includes academic, behavioral, and art-based interventions; and explores ethical and legal issues relating to students with anxiety. Filled with real-life examples, practical teaching tips, and creative advice for building connections with students, this book not only provides readers with the latest information about anxiety but also focuses on strategies to give educators the real tools they need to reduce the negative impact of anxiety in academic settings